Impacts of irrigation expansion on moist-heat stress based on IRRMIP results - Yi Yao; Agnès Ducharne; Benjamin I. Cook; Steven J. De Hertog; Kjetil Schanke Aas; Pedro F. Arboleda-Obando; Jonathan Buzan; Jeanne Colin; Maya Costantini; Bertrand Decharme; David M. Lawrence; Peter Lawrence; et al. (Nature Communications)
Abstract Irrigation rapidly expanded during the 20 t h century, affecting climate via water, energy, and biogeochemical changes. Previous assessments of these effects predominantly relied on a single Earth System Model, and therefore suffered from structural model uncertainties. Here we quantify the impacts of historical irrigation expansion on climate by analysing simulation results from six Earth system models participating in the Irrigation Model Intercomparison Project (IRRMIP). Results show that irrigation expansion causes a rapid increase in irrigation water withdrawal, which leads to less frequent 2-meter air temperature heat extremes across heavily irrigated areas (≥4 times less likely). However, due to the irrigation-induced increase in air humidity, the cooling effect of irrigation expansion on moist-heat stress is less pronounced or even reversed, depending on the heat stress metric. In summary, this study indicates that irrigation deployment is not an efficient adaptation measure to escalating human heat stress under climate change, calling for carefully dealing with the increased exposure of local people to moist-heat stress.